A brief review on slow breathing practices and their association with psychophysiological effects and behavioral outcome - Nordin, Simbak; Khairi, Che Mat; Vidya, Bhagat (2020)
The breathing technique helps in anxiety management based on psycho-physiological correlates of slow breathing. The psycho-physiological changes due to the brain-body interaction are observed in normal individuals and anxiety patients. Patients trained and practicing diaphragmatic breathing technique and people who practice breath control by meditation have demonstrated slowing down of breath frequency. There are limited studies regarding mechanisms involving breath control and its psychophysiological effects. This review study is aimed at exploring psychophysiological mechanisms underlying slow breathing techniques followed in the east and west and their effects on healthy subjects. This literature review completed using electronic databases such as PubMed, Medline, and Scopus databases using keywords such as breathing techniques, psychophysiology of breath control, meditation and breath control, relaxation and breathing technique, cardiorespiratory fitness and relaxing the nervous system. The current study analyzed 62 articles from the year 1970 to 2019. The main effects of slow breathing techniques have proven psychophysiological correlation paving to psychological/behavioral outputs that had increased comfort, relaxation, pleasantness, vigor and alertness, and reduced symptoms of arousal, anxiety, depression, anger, and confusion.